Central bank intervention in the inflation targeting - Borivoje D. Krušković (Journal of Central Banking Theory and Practice, 2022)
This paper analyses the impact of central bank interven-tions in the inflation targeting regime. The results of empirical stud-ies in this paper show if there is a shock of the exchange rate, which would lead to depreciation of the exchange rate, a central bank may decide to mush instability on the foreign exchange market with foreign exchange interventions, thereby preventing the sudden ex-change rate depreciation, which would then require a smaller reac-tion by the interest rate. Namely, through foreign exchange interven-tions, the central bank greatly absorbs the depreciation shock and, consequently, inflation is lower. As a result of lower price growth, the need for a monetary policy response to an interest rate is also lower. Based on this example, we can see that central bank intervention in some cases can be very useful in order to correct disturbances in the foreign exchange market. Therefore, some central banks accumulate foreign exchange reserves at a very high level so as to have enough space for foreign exchange intervention, without the risk of falling foreign exchange reserves below the optimum level.
Keywords: E52; E58; F31; C50; G15; 330; central bank intervention; inflation targeting; foreign ex-change reserves; exchange rate